O-GlcNAc: Regulator of Signaling and Epigenetics Linked to X-linked Intellectual Disability - Konzman, Daniel; Abramowitz, Lara K.; Steenackers, Agata; Mukherjee, Mana Mohan; Na, Hyun-Jin; Hanover, John A. (Frontiers in Genetics, 2020)
Cellular identity in multicellular organisms is maintained by characteristic transcriptional networks, nutrient consumption, energy production and metabolite utilization. Integrating these cell-specific programs are epigenetic modifiers, whose activity is often dependent on nutrients and their metabolites to function as substrates and co-factors. Emerging data has highlighted the role of the nutrient-sensing enzyme O-GlcNAc transferase (OGT) as an epigenetic modifier essential in coordinating cellular transcriptional programs and metabolic homeostasis. OGT utilizes the end-product of the hexosamine biosynthetic pathway to modify proteins with O-linked β-D-N-acetylglucosamine (O-GlcNAc). The levels of the modification are held in check by the O-GlcNAcase (OGA). Studies from model organisms and human disease underscore the conserved function these two enzymes of O-GlcNAc cycling play in transcriptional regulation, cellular plasticity and mitochondrial reprogramming. Here, we review these findings and present an integrated view of how O-GlcNAc cycling may contribute to cellular memory and transgenerational inheritance of responses to parental stress. We focus on a rare human genetic disorder where mutant forms of OGT are inherited or acquired de novo. Ongoing analysis of this disorder, OGT- X-linked intellectual disability (OGT-XLID), provides a window into how epigenetic factors linked to O-GlcNAc cycling may influence neurodevelopment.